Sungai : Sains dan teknologi melestari komuniti - Mohamad, Effendi; Mohd Aras, Mohd Shahrieel (Penerbit UTeM Press, 2024)
This book is one of the results of the University for Society (U4S) program based on the concept of "Redesign University Higher Education: University, Industry and Community Engagement", and supports the Malaysian Education Development Plan (PT) 2015-2025 where the "Quadruple Helix Engagement Model" becomes the main axis to the U4S concept.